Использование информационных технологий в преподавании теории механизмов и машин - Мацюк, И. Н.; Шляхов, Э. М. (My University, 2014)
В работе описан опыт использования Mathcad в преподавании теории механизмов и машин на кафедре основ конструирования механизмов и машин Национального горного университета.

An experience of MathCad usage in teaching of theory of mechanisms and machines at National Mining University is described in the paper.
The use of information technologies in teaching of theory of mechanisms and machines
Keywords: векторные уравнения; vector equations; плоские рычажные механизмы; flat rod mechanisms; анализ механизмов; analysis of mechanisms; методы векторной алгебры; methods of vectorial algebra; Mathcad